Analysis of the Application of Pharmaceutical Service Standards and Patient Satisfaction with Accreditation Status and Types of Services - Tarigan, Betharina Br; Dalimunthe, Aminah; Nasution, Azizah; Harahap, Urip; Khairunnisa, Khairunnisa (Journal La Medihealtico, 2023)
Accreditation is a method to improve the quality of health services, so that it is expected that the services provided are in accordance with established regulations. This study aims the implementation of Pharmaceutical Service Standards (PCSs) and patient satisfaction on accreditation status and types of PHCs in Deli Serdang Regency, Sumatera Utara. This descriptive analytical cross-sectional study was conducted to analyze pharmacy services at PHCs (n=34) in Deli Serdang Regency. The reference used is the Checklist for PCSs based on direct observations and interviews with the person in charge of pharmacy and the Patient Satisfaction Questionnaire. The data obtained were analyzed using SPSS version 22. The results on the value of a total score PCSs showed 41-90, with the highest level of patient satisfaction is the very satisfied category is 65.90%.The correlation test was analyzed using the Chi-Square test with a significance limit of p<0.05, the correlation of accreditation status to the implementation of PCSs showed a value of p=0.304, the correlation of the type of service to the implementation of PCSs showed a value of p=0.591, the correlation of the accreditation status of PHCs to the level of satisfaction patient value showed a value of p=0.000. This study concluded that the accreditation status of the PHCs does not affect implementation of PCSs, the type of PHCs service does not affect implementation of PCSs and the accreditation status of the PHCs has an effect on the level of patient satisfaction in Deli Serdang Region, Sumatera Utara.